STRUKTUR PENYAJIAN TARI BELENGGANG UPACARA BAYAR NIAT MASYARAKAT DAYAK KANAYATN DESA PAKU RAYA - Heri Saputra; Imma Fretisari; Asfar Muniir (Universitas Tanjungpura, 2019)
AbstractThis research was motivated by the desire of researcher to know the structure of the presentation of Belenggang dance in the ceremony of paying intention to the Dayak Kanayatn community in Paku Raya Village of Kuala Behe District, Landak Regency, to describe the presentation structure that has characteristics both in terms of motion, music, make up and clothing, and poetry in it. . This research includes some theories such as dance structure presentation, elements of dance presentation and implementation.This research used descriptive method with a qualitative research form and choreographic as approach of the research. This research contained some datas about facts of structure of presentation of the dance in the paying intention ceremony in the Dayak Kanayatn community in Paku Raya Village, Kuala Behe District, Landak regency. The data were analyzed qualitatively, with Mr. Bulup, Mr. Daud and Mr. Sudimanto as the dancers, shamans and musicians who were knowing better about the Structure of Belenggang Dance Presentation.Based on data analysis, it can be concluded as follows. The structure presentation of the Belenggang dance is the arrangement of a single presentation or appearance which has three main parts contained in the presentation structure, such as the beginning, middle and the end. The main elements of structure of presentation such as dance moves that was intend to describe something known as meaningful motion, floor design on the lines through which dancers, accompaniment music, poetry, themes, make-up and clothing, as well as venues are danced in open space because this dance was a dance that depicts gratitude towards Jubata. Keywords: Structure of Performance, Belenggang Dance, Landak